Indonesia Sistem Monitoring Kesehatan Tanaman Hidroponik Portable di Dalam Ruangan dengan Integrasi Smartphone Berbasis IoT untuk Pertanian Cerdas - Muhammad Rifal Rifdiansyah; Pita Hutabalian; Nadiyah Nur Rafifah; Susilawati, M.Si (Peneliti.net, 2026)
Monitoring system based on the Internet of Things (IoT) was developed using an ESP32 microcontroller and the Blynk application. The system integrates temperature and humidity sensors (DHT22), a soil moisture sensor (YL-69), and a light sensor (LDR), transmitting real-time data to a smartphone. The test results indicate that the system accurately and reliably monitors indoor plant conditions. Therefore, this system supports ef icient and water-saving smart farming practices that can be easily implemented by urban farmers and communities.